Freedom of Religion or Belief: Analyzing Indonesia’s Laws on Religious Minorities and Social Justice (Indonesian Minority Justice Review, 2024)
This paper critically examines Indonesia's legal framework concerning religious minorities and its alignment with the principles of social justice. Although Indonesia is officially committed to religious freedom, the reality for religious minorities—including Christians, Hindus, Buddhists, and adherents of indigenous beliefs—is often marked by discrimination, violence, and legal limitations. The study analyzes Indonesia’s legal provisions, such as the 1945 Constitution, the Law on Religious Harmony (2006), and the 2013 Joint Ministerial Decree on Religious Organizations, which aim to protect religious freedom. The paper assesses how these laws impact religious minorities, considering both legal protections and the limitations imposed by local governments and societal norms. Through a combination of legal analysis, interviews with religious leaders, and case studies of religious conflict, the research reveals significant gaps in the protection of religious minorities, particularly in relation to the construction of places of worship, freedom of expression, and interfaith relations. The findings suggest that while legal protections exist, their implementation is often selective, and religious minorities continue to face marginalization and harassment. The paper concludes by proposing legal reforms to ensure more robust protections for religious minorities and to promote a culture of interfaith dialogue and tolerance in Indonesian society.